2021
DOI: 10.1029/2020jc016962
|View full text |Cite
|
Sign up to set email alerts
|

The South Atlantic Meridional Overturning Circulation and Mesoscale Eddies in the First GO‐SHIP Section at 34.5°S

Abstract: The variability of the Atlantic meridional overturning circulation (AMOC) has considerable impacts on the global climate system. Past studies have shown that changes in the South Atlantic control the stability of the AMOC and drive an important part of its variability. That is why significant resources have been invested in a South (S)AMOC observing system. In January 2017, the RV Maria S. Merian conducted the first GO-SHIP hydrographic transect along the SAMOC-Basin Wide Array (SAMBA) line at 34.5°S in the So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 99 publications
6
23
2
Order By: Relevance
“…The relationship between temperature and AMOC enables the use of satellite sea surface temperature as a proxy for long‐term reconstructions of AMOC strength (Caesar et al., 2018; Manta et al., 2021), which can be compared to the estimations obtained with global climate numerical models (Caesar et al., 2018; Fraser & Cunningham, 2021). Longer term reconstructions and projections from proxies and high‐resolution climate models display a decline in the strength of the AMOC by 15% (Caesar et al., 2018) and 30% (Rahmstorf et al., 2015) since the 1950s, in the frame of a consistent weak AMOC for the last 150 years (Thornalley et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between temperature and AMOC enables the use of satellite sea surface temperature as a proxy for long‐term reconstructions of AMOC strength (Caesar et al., 2018; Manta et al., 2021), which can be compared to the estimations obtained with global climate numerical models (Caesar et al., 2018; Fraser & Cunningham, 2021). Longer term reconstructions and projections from proxies and high‐resolution climate models display a decline in the strength of the AMOC by 15% (Caesar et al., 2018) and 30% (Rahmstorf et al., 2015) since the 1950s, in the frame of a consistent weak AMOC for the last 150 years (Thornalley et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…However, the central and intermediate waters were the focus of this study, as significant decadal C ant changes have been observed mainly in these waters (Wanninkhof et al., 2010; Woosley et al., 2016). Guided by earlier water mass definitions (Hernández‐Guerra et al., 2019; Manta et al., 2021; Stramma & England, 1999) the first 1100 m of the water column were split into two layers (hereafter referred to as central and intermediate water layers) using the neutral density (γ n ) values extracted from the GLODAPv2‐2021 database (calculated following Jackett & McDougall, 1997). The central water layer was defined by γ n boundaries between 26.2 kg m −3 and 27.1 kg m −3 , which goes from ∼150 to ∼750 m, and is mainly composed of the South Atlantic Central Water (SACW).…”
Section: Methodsmentioning
confidence: 99%
“…However, in other studies, such as Manta et al. (2021), Lower Circumpolar Deep Water (LCDW) occupies the range 28.1–28.27 γ n while AABW is more narrowly defined as water denser than 28.27 γ n . By that definition there is no AABW east of 30°W.…”
Section: Resultsmentioning
confidence: 91%